Penerapan Reward dan Punishment dalam Meningkatkan Prestasi Belajar Siswa di SMA Negeri 5 Kepulauan Sula - Sapsuha, Irma; Wallly, Monika (Sekolah Tinggi Agama Islam Babussalam Sula, 2024)
This study aims to analyze the application of rewards and punishments in improving student achievement at SMA Negeri 5 Kepulauan Sula. The issue of low student motivation and discipline necessitates a strategic approach to address these challenges. Using qualitative methods, data were collected through interviews, observations, and document analysis. The results indicate that rewards enhance students' motivation and self-confidence, while punishments reinforce discipline and positive behavior. The combination of these methods creates a conducive learning environment, increasing students' active participation and academic performance. This study suggests the implementation of rewards and punishments tailored to local characteristics to enhance the effectiveness of educational strategies. The contribution of this research is to provide recommendations to educators in creating a more productive learning environment that supports the holistic development of students